Multicultural Da'wah in the Digital Realm: Spreading Inclusive Islamic Messages in the Virtual World - Sitti Hamsiyah; Mahmuddin Mahmuddin (CV. Publikasi Indonesia, 2026)
The emergence of exclusive and intolerant religious narratives in the digital space has the potential to erode the multicultural spirit in Indonesia. In the context of da'wah, such a reality requires effective strategies as an effort to prevent and minimize division. However, the situation in various da'wah spaces still shows partiality, meaning the da'wah message is not delivered in accordance with the cultural, social, and digital literacy conditions of the audience. This remains a challenge to be addressed in da'wah, especially in cyberspace. Based on this reality, this study aims to examine the concept of inclusive da'wah as a strategy capable of accommodating differences and preventing religious exclusivism in cyberspace. The research method uses a qualitative approach with a literature review method. The results show that inclusive da'wah in the digital realm is conducted based on constructive, educational, participatory, and contextual communication. Inclusive da'wah in the virtual world can be applied to digital media such as social media, YouTube, podcasts, blogs, and websites. This research has implications for the development of a more inclusive and responsive digital da'wah model.